2021
DOI: 10.1177/23259671211027543
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model for Primary Anterior Cruciate Ligament Injury Using Artificial Intelligence

Abstract: Background: Supervised machine learning models in artificial intelligence (AI) have been increasingly used to predict different types of events. However, their use in orthopaedic surgery has been limited. Hypothesis: It was hypothesized that supervised learning techniques could be used to build a mathematical model to predict primary anterior cruciate ligament (ACL) injuries using a set of morphological features of the knee. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Included were 50 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In the continuous updating of the CNN model, a CNN can also achieve better accuracy and sensitivity. Moreover, the input data of the model are no longer limited to similar data sets, and the classification criteria are no longer divided into whether the ACL is injured, or uninjured, so we must turn to the prediction of ACL injuries [ 28 ] and ACL reconstruction failures. However, the process of transforming clinical trial result and applying this technology in a such a way that helps clinicians remains stagnant.…”
Section: Discussionmentioning
confidence: 99%
“…In the continuous updating of the CNN model, a CNN can also achieve better accuracy and sensitivity. Moreover, the input data of the model are no longer limited to similar data sets, and the classification criteria are no longer divided into whether the ACL is injured, or uninjured, so we must turn to the prediction of ACL injuries [ 28 ] and ACL reconstruction failures. However, the process of transforming clinical trial result and applying this technology in a such a way that helps clinicians remains stagnant.…”
Section: Discussionmentioning
confidence: 99%
“…Christensen et al 17 found a mean posterior tibial slope of 8.4° among patients in whom the ACL reconstruction failed within 2 years of the surgical procedure, compared with 6.5° among patients with no evidence of graft failure. An elevated posterior tibial slope has also been identified in patients with primary ACL injury in comparison with sex-matched controls with no history of ACL injury 22 .…”
Section: Joint Alignmentmentioning
confidence: 96%
“…Tamini et al employed supervised ML models to construct a predictive mathematical model for primary ACL injuries, using a set of knee morphological characteristics [21]. Preoperative MRI scans were utilized to measure the anteroposterior lengths of the medial and lateral tibial plateaus, as well as the lateral and medial bone slope, lateral and medial meniscal slope, and lateral and medial menisci.…”
Section: Predictionmentioning
confidence: 99%